Factors Associated with Nursing Student Satisfaction with Their Clinical Learning Environment at Wolkite University in Southwest Ethiopia - Ayana Benti Terefe; Tolesa Gemeda Gudeta (Hindawi Limited, 2022)
Background. The clinical learning environment has been defined as "an interactive network of strengths within the clinical environment that influence the clinical learning outcomes of students. Understanding students' level of satisfaction with their clinical learning environment is crucial to ensuring the required teaching and learning process. Therefore, this study was designed to assess the level of satisfaction with the CLE among nursing students at the Wolkite University of Ethiopia. Methods. A cross-sectional study was conducted at Wolkite University. This study was carried out in March 2022 on 208 student nurses selected by purposive and convenient sampling techniques. This study used the English version of the Clinical Learning Environment and Supervision + Nurse Teacher (CLES + T) evaluation scale. The collected data were cleaned, coded, and entered into Epi data 3.1, and then, statistical analyses were performed using SPSS version 26. Bivariate and multivariable logistic regression models were used to identify factors associated with the satisfaction level of nursing students towards CLE. Adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were calculated, and p values < 0.05 were considered to indicate statistical significance. Results. More than half of the study participants were females, and nearly half (50.5%) of the participants were in year three of the nursing program. The study found that 39.9% (95%CI: 32.2%, 46.6%) of students were satisfied with their CLE. Factors that had a significant association with the satisfaction level of nursing students towards CLE were gender (female students) (AOR = 16.053 (6.397, 40.286)), year of study (4th year) (AOR = 6.296 (2.679, 14.796)), and the type of the hospital in which their last clinical placement was held (at a primary hospital) (AOR = 2.961 (1.122, 7.815)). Conclusion. Effective nursing education programs need to be developed to increase satisfaction with clinical practice and to promote positive emotional regulation in nursing students. Nurse practitioners and managers should be aware of their important role in the professional development of students and their satisfaction with clinical placements.